Application of double glazed façades with horizontal and vertical louvers to increase natural air flow in office buildings. (1st June 2020) - Pourshab, Nasrin; Tehrani, Mehdi Dadkhah; Toghraie, Davood; Rostami, Sara
Abstract: The results of previous researches clearly indicate that the main concern in applying double skin façades (DSF) is overheating of the cavity and increasing the cooling energy consumption in warm seasons. The present study intends to consider the excessive heat trapped between two skins of double glazed façades in hot arid climates as a driving force to reinforce the natural airflow across the floors of an office building. To meet this purpose, numerical simulation of airflow and heat transfer inside the cavity of the double glazed façades and the adjacent floors, as well as the effect of different types of solar shading systems in horizontal and vertical modes on the airflow has been investigated using the CFD technique. The results show that the stack effect formed inside the cavity has enough power for air suction from the floors of the building and reinforcement of the natural airflow. The type of shading device has a significant effect on the airflow behavior and the heat transfer rate in the facade. In double skin facades with horizontal louvers, the buoyancy forces inside the cavity are stronger and the ventilation rate in the building floors is higher than the model with vertical louvers. On the other hand, due to the stronger convective flow in the cavity with horizontal louvers, the heat flux on the interior glass is higher than the cavity with vertical louvers and part of the heat inside the cavity is transmitted through the interior skin to the occupied spaces. Highlights: Numerical simulation of air flow and heat transfer in a naturally ventilated four-story office building. Using of DSF with horizontal and vertical louvers in the hot and arid climate. Stack effect formed inside the cavity has enough power for air suction in the floors.